Contrasting Symbiotic Patterns in Two Closely Related Lineages of Trimembered Lichens of the Genus Peltigera - Pardo-De la Hoz, Carlos José; Magain, Nicolas; Lutzoni, François; Goward, Trevor; Restrepo, Silvia; Miadlikowska, Jolanta (Frontiers in Microbiology, 2018)
Species circumscription is key to the characterization of patterns of specificity in symbiotic systems at a macroevolutionary scale. Here, a worldwide phylogenetic framework was used to assess the biodiversity and symbiotic patterns of association among partners in trimembered lichens from the genus Peltigera, section Chloropeltigera. We sequenced six loci of the main fungal partner and performed species discovery and validation analyses to establish putative species boundaries. Single locus phylogenies were used to establish the identity of both photobionts, Nostoc (cyanobacterium) and Coccomyxa (green alga). Distribution and specificity patterns were compared to the closely related clade, section Peltidea, which includes mainly Peltigera species with trimembered thalli. For section Chloropeltigera, eight fungal species (including five newly delimited putative species) were found in association with nine Nostoc phylogroups and two Coccomyxa species. In contrast, eight fungal species (including three newly delimited putative species) in section Peltidea were found in association with only four Nostoc phylogroups and the same two Coccomyxa species as for section Chloropeltigera. This difference in cyanobiont biodiversity between these two sections can potentially be explained by a significantly higher frequency of sexual reproductive structures in species from section Chloropeltigera compared to section Peltidea. Therefore, horizontal transmission of the cyanobiont might be more prevalent in Chloropeltigera species, while vertical transmission might be more common in Peltidea species. All Peltigera species in section Chloropeltigera are generalists in their association with Nostoc compared to more specialized Peltigera species in section Peltidea. Constrained distributions of Peltigera species that associate strictly with one species of green algae (Coccomyxa subellipsoidea) indicate that the availability of the green alga and the specificity of the interaction might be important factors limiting geographic ranges of trimembered Peltigera, in addition to constraints imposed by their interaction with Nostoc partners and by climatic factors.